4. ELEVATING MSME: NAVIGATING BARRIERS AND STRATEGIC INITIATIVES IN THE HALAL INDUSTRY - Arsad, Syahiza; Ghazali, Faizatul Hasliyanti; Said, Roshima; Ismail, Rushda Hadzira; Yusoff, Wan Sallha (Journal of Islamic, Social, Economics and Development, 2024)
Since the establishment of Malaysia as the world's halal hub, the halal industry has been seeing significant growth. Despite this, the issue of halal products and Muslim products has been distinct since the emergence of halal products, which are characterised by the presence of a halal label displayed on the product's packaging or at the retail store, and the fact that the product may originate from an entrepreneur that is not Muslim. The term "Muslim products" refers to goods that are produced by Muslim entrepreneurs. Although some of these goods do not bear the halal label, they are typically sold based on the belief that Muslims are obligated by their religious beliefs to sell only these kinds of goods. There is a dispute that emerges when Muslim products are unable to reach established supermarkets until there is a Buy Muslim First (BMF) campaign among the individual entrepreneurs that sell Muslim products. This led to the number of halal-certified companies from Bumiputera entrepreneurs was only 38.7% and only 6% contribution to halal export. As a result, this concept paper will conduct an in-depth analysis of the existing literature regarding the significant barriers faced by micro, small, and medium-sized enterprises (MSMEs) to participate in the halal industry namely halal certificate, marketing/promotion, branding and packaging, financial capability and management capability. The findings of this study are expected to help the government's objective to achieve Strategic Thrust 6: producing more home-grown halal champions and Strategic Thrust 7: facilitating more competitive Bumiputera participation in the Halal industry.